On intersections of normal subgroups in groups - Kulikova, O.V. (Algebra and Discrete Mathematics, 2004)
The paper is a generalization of [2]. For a group H = ‹A|O›, conditions for the equality Ñ₁ ∩ Ñ₂ = Ñ₁, Ñ₂] are given in terms of pictures, where Ñi is the normal closure of a set R¯ i ⊂ H for i = 1, 2.